Production of monoclonal antibody based on HA and NP protein of bat H18N11 influenza virus in mice - Deb Nath, Nirmalendu (Kansas State University, 2021)
Influenza A viruses (IAVs) usually circulate in the waterfowl, but some of them with the capability to cross the species-specific boundaries and infect the mammalian host can cause severe zoonotic outbreaks. The sequences of H17N10 and H18N11 subtypes of bat IAVs have been identified, but the resource of these bat IAVs are still limited. Among eight proteins of bat IAVs, the surface glycoprotein HA and internal protein NP are important and can act as immunogenic proteins. They can be a good target for further research to study bat IAVs. Therefore, in this study, we produced a panel of NP and HA protein-specific monoclonal antibodies (mAbs) of bat H18N11 influenza virus. We immunized the BALB/C mice with baculovirus expressed HA and NP protein and then produced hybridoma cells by fusing spleen B cells with myeloma SP2/0 cells. We further tested these mAbs to identify the characteristics by using different immune assays. Six NP protein-derived mAbs were found specific and weakly bound with NP protein of H18N11 in immunofluorescence assay (IFA). These mAbs only reacted with NP protein of H18N11 virus other than those of conventional IAVs in IFA. In contrast, all the HA-specific mAbs failed to be reactive with HA of H18N11 in IFA. Isotyping of the mAbs was characterized by ELISA, and the results showed that all the NP-specific mAbs belong to IgG3. These NP-protein-derived mAbs specifically recognized the possible epitope with the amino acid sequence of position 445-458. To our surprise, all the NP-specific mAbs were not found reactive in the western blotting (WB) assay to detect the NP protein of H18N11 virus. Though the NP-specific mAbs were not specific in WB, they could detect NP of H18N11 by using IFA and ELISA. Therefore, the panel of NP mAbs can be a useful tool to study bat IAVs.
Keywords: Bat Influenza virus; Monoclonal antibody; Hybridoma; Western blotting; ELISA; IFA